Artikel Review : Pengaruh Edukasi Terhadap Manajemen Diri Pasien Diabetes Mellitus (DM) - Alfi Dwi Seviah; Fitria Ayu Kusumaningtyas; Nabyla Qutrun Nada; Amelia Saputri Ginting; Natalia Abuk Bria; Alfu Laila; Bella Fevi Aristia; Eka Putri Nurhidayah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Diabetes Mellitus (DM) is a global health problem that continues to increase, especially in Indonesia. This disease is characterized by high blood glucose levels due to impaired insulin metabolism. This article aims to evaluate the effect of pharmaceutical education, particularly through booklets, pocket books, and counseling, on the self-management of type 2 DM patients. The results of the study show that pharmaceutical education is significant in improving patients' knowledge, compliance, and quality of life. Education through booklets and pharmacy counseling helps patients understand the importance of managing diet and physical activity. Although education has been shown to improve control of blood glucose levels, many patients still face challenges in consistently implementing self-management. Therefore, a more integrated and sustainable educational approach is needed to support DM patients in managing their condition effectively.